Education and assistance in hydroponic plant cultivation for strengthening the self-reliant economy - Septi Budi Sartika; Chandrika Rahmania Cahyani (University of Merdeka Malang, 2023)
Assistance with a hydroponic cultivation theme towards strengthening the self-reliant economy of Sukoreno Village is a manifestation of awareness in contributing to the development of a more modern agricultural system and Micro, Small, and Medium Enterprises (MSMEs) within the community. The partners for this activity are 10 members of the Sukoreno Village Youth Organization (